Polizze assicurative a tutela dei partecipanti alle sperimentazioni cliniche dei medicinali ed esclusione dei danni concausati da infezione da Covid-19 (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
An insurance policy, relating to a drug clinical trial protocol, examined by an ethics committee limits the insurer liability to any damage or injury caused directly or indirectly or just in connection with any Coronavirus. According to the Italian law, such provision shall be considered inadmissible. Should an experimental protocol be approved with such a limit of liability, the participants involved in the trial, the healthcare institution in which it takes place and any healthcare personnel involved must be informed in detail.
Keywords: Ethics committees; clinical trials; experimental protocols; insurance coverage; Covid-19